MASTERA and Generation-Y: The Role of Literature in Southeast Asia (Malay Literature, 2023)
The Southeast Asia Literary Council, or MASTERA (Majlis Sastera Asia Tenggara), is a regional body representing five countries, namely Brunei Darussalam, Indonesia, Malaysia, Singapore and Thailand. MASTERA was established in 1996 with the main aim to weave strong literary relations among its member countries. Each year, the council organizes its agendas through various activities in conjunction with its annual MASTERA council meeting. Among them are the International Southeast Asia Literary Seminar (Seminar Antarabangsa Kesusasteraan Asia Tenggara or SAKAT), MASTERA Comparative Literature Lecture Series and MASTERA Writing Programme of various genres, including poetry, short story, essay, stage drama and novel. Although MASTERA was established more than two decades ago by the pioneers, the majority of its current active participants are young literary enthusiasts who belong to Generation-Y. This positive scenario is very constructive in all aspects and the participation of Generation-Y should be given appreciation and attention accordingly as they will be the next bearers of MASTERA. In view of this, a study has been conducted to observe the potentials of MASTERA to provide for its members from Generation-Y based on their literary needs in South-east Asia. The study on the younger generation of MASTERA members will be reflected in this article, which describes the challenges faced by MASTERA in terms of the platform and content in relation to Industrial Revolution 4.0 (4IR). The findings will enable the study to forward suggestions in the aspects of regional philosophy, including its practice.Full text: PDF